UrbanClap : a marketplace for on-demand services - Abhishek; Mukherjee, Saral; Patra, Yogita (London : Indian Institute of Management, Ahmedabad, 2020)
UrbanClap is a marketplace for on-demand services available through a smartphone app. It was established in October 2014 to bring the unorganized sector workforce into the mainstream using the power of technology. Initially, UrbanClap-developed as a horizontal marketplace-faced intense competition from existing and new players operating in the hyperlocal service space. It competed in the on-demand service marketplace by categorizing its services into a lead-generation business (connecting the customer with the service provider and charging a fee for matchmaking) and a fulfillment business (taking end-to-end responsibility for service delivery quality). After three and a half years of operations, UrbanClap's co-founders wondered whether they should close the lead-generation business and focus on the fulfillment business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; On-demand marketing